Medical instrumentation application and design - Webster, John G. 1932-; Nimunkar, Amit J.; Clark, John W. (John William) 1936- (Wiley, 2020)
"This book provides biomedical engineers with the premiere reference on medical instrumentation as well as a comprehensive overview of the basic concepts. The revised edition features new material on infant apnea monitors, impedance pneumography, the design of cardiac pacemakers, and disposable defibrillator electrodes and their standards. Each chapter includes new problems and updated reference material that cover the latest medical technologies. The chapters have also been revised with new material in medical imaging, providing biomedical engineers with the most current techniques in the field. This well-established text describes the principles, applications and design of the medical instrumentation most commonly used in hospitals. Because equipment changes with time, the authors stress fundamental principles of operation and general types of equipment. Design principles are emphasized so that a scientist with only some background in electronics can gain enough information to design instruments that may not be commercially available."